Exploring Bonding Properties and Photophysical Behavior of Naphthoquinone-Based Rhenium(I) Tricarbonyl Complexes: A Combined Experimental and Theoretical Approach - Gomez-San Martin, A; Gomez-San Martin, A; Jara-Reyes, G; Jara-Reyes, G (American Chemical Society, 2025)
In this work, we describe the synthesis, characterization, and spectroscopic properties of four new rhenium(I) tricarbonyl complexes bearing a pyridyl imidazole-naphthoquinone (Py-Im-Nq) ligand. The spectroscopic, X-ray, and electrochemical analyses confirm the formation of neutral complexes in all cases. Although the Py-Im-Nq ligand possesses two distinct chelating fragments, we observed a selective formation of the N,N-isomer rather than the N,O-coordination. EDA calculations revealed that the origin of the N,N-linkage isomerism results from more favorable electrostatic interactions present in the N,N-coordination. Furthermore, EDA-NOCV analysis indicated that the bonding situation in these complexes can be described by the Dewar−Chatt−Duncanson model, providing a quantitative characterization of the donation and back-donation interaction components in these complexes. Finally, we examined the spectroscopic behavior (UV−vis and photoluminescence) of these new rhenium(I) complexes in solution. The characterization of the excited states was performed using TD-DFT and density difference isosurfaces. It was found that, in contrast to typical fac-[Re(NN)(CO)3L]0/+ systems, the low-lying transitions exhibit intraligand (IL) character, with charge transfer predominantly occurring from the imidazole ring to the carbonyl group in the quinone moiety. In contrast, a mixed metal-to-ligand charge transfer (MLCT)/IL transition is assigned to the electronic excitation at shorter wavelengths. © 2025 American Chemical Society.